Identification of going-concern risks in csr and integrated reports of polish companies from the construction and property development sector - Elżbieta Izabela Szczepankiewicz (Risks, 2021)
The question of non-financial and risk disclosures in corporate annual statements has been discussed globally for over a decade. The stakeholders of socially responsible organisations report a constantly growing demand for financial and non-financial information, including that related to threats and risks connected to the organisation's activity. The aim of this paper is to determine whether companies from the construction and property development sector disclose financial risk in a CSR or integrated reports, and whether it is possible to assess going-concern risks based on the reports. The author analysed the content of selected CSR and integrated reports to describe the scope and structure of going-concern risk information in Polish companies from the construction and property development sector. The author reached two key empirical findings. Firstly, the results may suggest that companies are at different stages of the process of adopting integrated reporting, depending on the year of issue of the first CSR report. Secondly, less than half of the analysed companies disclose their financial data and risk, as well as describe their risk management systems. The study also shows that the 'soft' solutions set out in the regulations give companies considerable freedom in disclosing risk information, which is sometimes counterproductive. Therefore, it is of key importance to develop a single integrated standard for risk disclosures. In this paper, the author demonstrates a logical process of reasoning ensuing from the literature review through empirical research down to the implementation stage of conceptual model for disclosures on financial and going-concern risks in CSR and integrated reports. The present study makes a valuable contribution to CSR and integrated reporting theories and constitutes a breakthrough in identifying risks affecting socially responsible companies in Poland. The study fills a research gap in the area of non-financial (including information on risk) disclosures in annual reports of listed companies and other companies from the construction and property development sector.
Keywords: 330; corporate social responsibility; CSR report; financial statement; going-concern risk; integrated report; risk